Pengaruh Kombinasi Dosis Pupuk Organik Cair (POC) Kulit Pisang Kepok dan Pupuk Urea Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) Varietas Nauli F1 Pada Sistem Vertikultur - Wilda Agustiani; Muharam Muharam; Bastaman Syah (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this research is to get the obtain a combination of liquid organic fertilizer kepok banana peel and urea fertilizer that gives the best influence on the growth and yield of pakcoy plant (Brassica rapa L.) varieties of Nauli F1. The research method used is an experiment method with a single factor Randomized Block Design (RBD) with 7 combinations of treatments and 4 replication, the trearment: A (LOF Banana Peel 0 ml/liter + Urea 0 kg/ha), B (LOF Banana Peel 0 ml/liter + Urea 300 kg/ha), C (LOF Banana Peel 300 ml/liter + Urea 0 kg/ha). D (LOF Banana Peel 300 ml/liter + Urea 300 kg/ha), E (LOF Banana Peel 300 ml/liter + Urea 200 kg/ha), F (LOF Banana Peel 100 ml/liter + Urea 300 kg/ha). G (LOF Banana Peel 100 ml/liter + Urea 200 kg/ha). The results showed there was significant on the provision of liquid organic fertilizers of banana peels and urea fertilizers on the average growth of plant height (14 dap, 21 dap, and 27 dap), the number of leaves (14 dap, 21 dap, and 27 dap), the diameter of the stems (7 dap, 14 dap, 21 dap, and 27 dap), root weight, leaf area, leaf area index and fresh weight. The treatment E (LOF Banana Peel 300 ml/liter + Urea 200 kg/ha ) obtained the best average results on the number of leaves and root weight meanwhile the treatment G (LOF Banana Peel 100 ml/liter + Urea 200 kg/ha) obtained the best average results against the height of the plant, stem diameter, leaf area, index of leaf area, and fresh weight of 58.61 grams/plant.